A comparative study of 0.25% levobupivacaine and 0.25% levobupivacaine with dexmedetomidine in ultrasound-guided transverse abdominis plane block for post-operative analgesia in infraumbilical surgeries - Dhanashree PJ,; Bammidi Muralikrishna,; Venkata Krishna Gollapalli,; Mahendran M, (Asian Journal of Medical Sciences, 2023)
Background: Transversus abdominis plane (TAP) block delivers excellent analgesia with few side effects. Previous research suggests that the efficacy and duration of the block can be increased by adding adjuvants such as dexmedetomidine to the local anesthetics. Aims and Objectives: To compare the post-operative analgesic effectiveness of 0.25% levobupivacaine and 0.25% levobupivacaine with dexmedetomidine 1 μg/kg in US-guided TAP block in infraumbilical surgery patients. Materials and Methods: Ultrasound-guided TAP block was given to sixty patients. Patients consented for infraumbilical surgery, and patients were randomly assigned to two groups: Group L received 20 mL of 0.25% levobupivacaine alone and Group LD received 20 mL of 0.25% levobupivacaine with dexmedetomidine 1 μg/kg. The efficacy of analgesia was measured in terms of degree and duration of analgesia; the post-operative pain was evaluated using a visual analog scale (VAS). The Chi-square test and Student’s t-test were used for statistical analysis. Results: Result shows that there is no statistically significant difference in gender, age group, weight, height, BMI, and type of surgery between groups, with a P=0.40, 0.83, 0.37, 0.59, and 0.93, respectively. In addition, there is no statistically significant difference in the duration of surgery between the groups (P=0.63). However, it was observed statistically significant differences in the onset of analgesia requirement, duration of effect of analgesia, and the total anesthesia consumption between the experimental groups with a P=0.001, 0.001, and 0.001, respectively. No significant difference in VAS was observed initially but was significant in later hours. Conclusion: Adding dexmedetomidine to 0.25% levobupivacaine enhanced the efficacy of the block and duration of post-operative analgesia compared to 0.25% levobupivacaine alone.